Implications of Ethical Conducts of Bureaucrats in Governance - Mendy, Ousu; Susilawati, Marietta (International Journal of Law and Public Policy (IJLAPP), 2025)
Over the years, the ethical conduct of bureaucrats in governance in the world has continued to threaten developments. Globally, much focus is given to international organisations and states with larger control in international affairs, and small states are often left in oblivion. This research aims to present an exposition of the legal implications of the ethical conduct of bureaucrats and the threats they pose to human rights as one of the litmus tests of modern governance. Government is at the centre of state development and therefore, the conduct of bureaucrats are quite topical, especially in this era when governance is globally at stake. In this research, the normative research method is used to examine secondary data that are germane to the subject. Journal articles, books, and state instruments or documents that regulate the conduct of government bureaucrats are examined. This research, therefore, concludes that unethical conducts of government bureaucrats violate human rights and therefore, the restorative justice system in the context of reimbursement of state resources acquired through unethical acts of bureaucrats is quite necessary in eliminating or mitigating it. This will help in determining its causes and create measures for preventing it by engaging victims, perpetrators, and affected communities.